Care, Gender, and Change in the Study of Sustainable Consumption: A Critical Review of the Literature - Godin, Laurence; Langlois, Justine (Frontiers in Sustainability, 2021)
In Western countries, moving towards more sustainable lifestyles often involves the disruption of well-established routines and habits in relation to consumption domains such as food, washing and cleaning, heating and cooling, transportation, and managing ‘stuff’ more generally. These activities are deeply embedded in our everyday lives and often tied to care, which is the work invested in maintaining the wellbeing of oneself and others. In this paper, we are interested in the ways sustainable consumption and care interlock within the household, how they relate to gender inequalities, and how change towards more sustainable lifestyles can both impact and be impacted by these inequalities. With this in mind, we conducted a critical review of the academic literature by analysing a corpus of 74 papers on household consumption and sustainability, paying particular attention to the role authors attribute to care and gender. The analysis shines light on the relational character of care and consumption, emphasizing the ways sustainable consumption is dependent on relationships within and outside the home. We suggest that care often acts as a barrier to the establishment of more sustainable consumption practice. Care work, per definition, upholds routines and habits while mobilizing the very resources that are needed to transform them. This insight invites us to rethink the role of households as a site for change. We suggest that the transition towards more sustainable consumption practices within the home relies on reducing and redistributing care work, transforming the world of work, and actively promoting an ethos of care that includes people, other beings, the material world and the planet.